Tricuspid Valve Myxoma: Features of Anatomy, Clinical Course, and Surgical Treatment - Rostyslav M. Vitovsky; Volodymyr V. Isaienko; Valentina P. Zakharova; Oleksandr A. Pishchurin; Andrii R. Vitovskyi; Igor V. Martyshchenko (Ukrainian Journal of Cardiovascular Surgery, 2025)
Relevance. Myxomas originating from the tricuspid valve (TV) are extremely rare. The literature describes myxomas that most often affect one leaflet of the TV. For the first time in our extensive practice, we encountered a myxoma of the right heart, which incredibly affected all leaflets of the tricuspid valve, which left no chance for its preservation.Aim. To present our experience in treating TV lesions in cardiac myxomas with a demonstration of a rare case of myxoma of probably congenital nature that affected all of its leaflets.Materials and methods. Among 922 patients with cardiac myxomas (CM), 70 (7.6%) patients with heart valve lesions due to this tumor were identified. The article presents the experience in treating tricuspid valve lesions in CM and a case of diagnosis and surgical treatment of TV myxoma of unusual localization in a 71-year-old woman. Diagnosis based on the use of echocardiography, coronary angiography and laboratory methods.Results. Isolated tricuspid valve insufficiency was observed in 30 patients. However, only 9 of these patients had a direct effect of myxoma on the function of the valve, which was located in the cavity of the right atrium (8) and right ventricle (1). In one case, a myxoma measuring 3.0×2.5 cm in a capsule with a smooth surface was found in the hole of the TV. The base of the tumor was located on the fibrous ring of the TV at the point of transition of the posterior leaflet into the septal with the involvement of all leaflets and all chords of this valve, which were included in the body of the tumor. The valve is significantly distorted with the inability to differentiate its leaflets. The tumor does not visually spread beyond the leaflets and fibrous ring. Given the very unusual location with an extremely unfavorable prognosis, the patient underwent surgery to remove the tumor and replacement the tricuspid valve.Conclusions. Myxomas of the ventricular septum are very unusual tumors with a diverse and unpredictable pattern of lesions that can be detected after the onset of symptomatic ventricular septum obstruction and signs of right ventricular heart failure. Despite significant lesions of the ventricular septum by a tumor process of a likely congenital nature, there is a possibility of a long asymptomatic course of the disease. Surgical treatment of TV myxoma involves removing the tumor with a high probability of replacing the affected valve.